2010
DOI: 10.1097/pcc.0b013e3181d90569
|View full text |Cite
|
Sign up to set email alerts
|

Reducing catheter-associated bloodstream infections in the pediatric intensive care unit: Business case for quality improvement

Abstract: The potential cost savings from reducing or eliminating catheter-associated bloodstream infections in the pediatric intensive care unit are significant. Elimination of catheter-associated bloodstream infections will directly reduce hospital costs, improve asset utilization, and most importantly, improve clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 26 publications
0
53
0
2
Order By: Relevance
“…Reducing CLABSI in children who would otherwise have short LOS not only saves more money, but also creates more turnover for revenuegenerating inpatient "first days" (assuming hospitals staff beds based on full census). 7 Along with prevention, we note potential saving in cost from the care management of CLABSI. There was a decrease in estimated cost of 11.8% ($111 852 in 2008 to $98 621 in 2011) of treating CLABSI but a negligible decrease in the cost of treating patients who do not acquire CLABSI over the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing CLABSI in children who would otherwise have short LOS not only saves more money, but also creates more turnover for revenuegenerating inpatient "first days" (assuming hospitals staff beds based on full census). 7 Along with prevention, we note potential saving in cost from the care management of CLABSI. There was a decrease in estimated cost of 11.8% ($111 852 in 2008 to $98 621 in 2011) of treating CLABSI but a negligible decrease in the cost of treating patients who do not acquire CLABSI over the same time.…”
Section: Discussionmentioning
confidence: 99%
“…6 A pediatric study found an attributable 2008 dollar cost of $33 039 per CLABSI in a sample of 22 critically ill children. 7 Quality improvement collaboratives, largely based in ICUs, have demonstrated that most CLABSIs are preventable. Michigan' s Keystone ICU project achieved and sustained a 60% reduction in CLABSI rates in adult ICUs, resulting in 1500 lives saved and $200 million in health cost savings over 18 months.…”
mentioning
confidence: 99%
“…CLABSI is one of the deadliest types of HAIs, with a mortality rate of 12%-25%. [11][12][13] Several factors, such as those related to the patients (immunodeficiency, need for extracorporeal life support or renal replacement therapy), CVC use (prolonged catheterization, type of CVC material, and anatomical site of insertion and handling), have been shown to increase the risk of CVC infection. 13 Here, we report an epidemiologic study about the CLABSIs in our PICU.…”
Section: Introductionmentioning
confidence: 99%
“…Catheter-related bloodstream infections (BSIs) are a common and serious complication of intravascular catheters and are associated with increased morbidity, mortality, length of hospital stay, and medical costs. [1][2][3][4][5] Although previous studies [6][7][8] indicated a low risk for infections associated with use of arterial catheters, recent studies [9][10][11] showed that the risk for arterial catheter-related infection was high, comparable to the risk associated with short-term use of central venous catheters. Compared with adult patients, children are more susceptible to nosocomial infection, and catheter-related BSI is considered the most common nosocomial infection in pediatric intensive care units (PICUs).…”
mentioning
confidence: 88%